Notary Role In Making The Deed Of Murabahah Financing On Islamic Bank (Review On Financing Agreement In Islamic Bank Of Central Java) - Anindia Inka Saputri; Agus Supriadi; Aryani Witasari (Jurnal Akta, 2020)
This study aims to determine the form of the contract and Murabahah financing mechanisms, to analyze the application of Sharia principles in Murabahah financing agreement, and to know the extent to which the role of the Notary in the Deed manufacture Murabahah Financing Agreement with Islamic Bank of Central Java. The results of this study show that: (1) The form of contract and Murabahah financing mechanism in Islamic Bank of Central Java refers to the provisions of Islamic Banking Act, BI (Bank Indonesia), FSA (Financial Services Authority) and DSN-MUI. (2) The application of Islamic principles in the financing agreement Murabahah in Bank Central Java Sharia has been in accordance with the Law of Islamic Banking and DSN-MUI, where financing based on Islamic principles that do not contain elements of usury, gambling, Garar, illegitimate and unjust.Keywords: Notary; Islamic Banking; Murabahah.